Liturgi Sakral yang Indah, Liturgi Indah yang Sakral - Sebastian Heatubun, Fabie (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
Celebrating the liturgy is still regarded as a duty. It was not particularly wrong. Even the church itself teaches and demands the faithful to attend the liturgy with some penalties if this obligation is ignored. Art is not so much friendly with the word 'duty'. The ‘ludic’ spirit of the liturgy cannot work with force. If the liturgy is seen as an art, then the basic character of beauty which has the dimensions of luring and tempting can indirectly educate the human person in order to be better able to 'bow down', to be more humble before the Mystery. Artistic liturgy will invite without force. The liturgy expects resignation, ‘sumarah’, an attitude of admiration, worship and awe. It is like Moses who had to take off his sandals to approach the burning bush. The beauty of the liturgy brings the meanings of encounter and promise. The beauty of the liturgy is supposed to free the human to understand all, to be understood readily, to be silent and to adore in the presence of the Mystery. In this case the liturgy makes humans more humane. Liturgy should bring back human to his or her true self, to his or her original nature.